2002
DOI: 10.4319/lo.2002.47.2.0343
|View full text |Cite
|
Sign up to set email alerts
|

Determination of apparent quantum yield spectra for the formation of biologically labile photoproducts

Abstract: Quantum yield spectra for the photochemical formation of biologically labile photoproducts from dissolved organic matter (DOM) have not been available previously, although they would greatly facilitate attempts to model photoproduct formation rates across latitudinal, seasonal, and depth-related changes in spectral irradiance. Apparent quantum yield spectra were calculated for two coastal environments from the southeastern United States using postirradiation bacterial respiration as a measure of total labile p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
120
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(131 citation statements)
references
References 54 publications
10
120
1
Order By: Relevance
“…Ziegler et al (2000) used the microbial uptake of tritiated leucine as their technique for measuring bioavailable photoproducts. In contrast, another recent study using a more sensitive technique involving microbial CO 2 production (Moran et al 2000, Miller et al 2002 indicated that the photodecomposition of CDOM produced by T. testudinum does produce bioavailable photoproducts . The difference in these results may reflect differences in the sensitivity of these 2 methods.…”
Section: Photobleaching Of Seagrass-derived Cdommentioning
confidence: 90%
See 1 more Smart Citation
“…Ziegler et al (2000) used the microbial uptake of tritiated leucine as their technique for measuring bioavailable photoproducts. In contrast, another recent study using a more sensitive technique involving microbial CO 2 production (Moran et al 2000, Miller et al 2002 indicated that the photodecomposition of CDOM produced by T. testudinum does produce bioavailable photoproducts . The difference in these results may reflect differences in the sensitivity of these 2 methods.…”
Section: Photobleaching Of Seagrass-derived Cdommentioning
confidence: 90%
“…Past studies have indicated that the polymeric substances that make up CDOM are not readily decomposed by microorganisms, but CDOM bioavailability changes on exposure to solar radiation (Mopper & Kieber 2000, Moran et al 2000, Ziegler & Benner 2000, Miller et al 2002). It has been known for years that absorption of solar UV radiation by terrestrially derived humic substances and CDOM results in a reduction in its light absorption and fluorescence (i.e.…”
Section: Photobleaching Of Seagrass-derived Cdommentioning
confidence: 99%
“…While there is a range of efficiencies with which the microbial community can access DOM (i.e. respiratory quotient RQ; Berggren et al, 2012), for the most part these boreal freshwater RQs fall within a relatively small range (0.5-2) and as such BOD can be used as an effective proxy for the biological reactivity or lability of the DOM (Miller et al, 2002;Asmala et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…The net effects of dissolved organic matter (DOM) photodegradation include: the alteration of DOM bioavailability (Moran and Zepp, 1997;Mopper and Kieber, 2000;Miller et al, 2002); the bleaching of CDOM colour (Del Vecchio and Blough, 2002;Helms et al, 2008); and the production of a suite of photoproducts, including CO 2 and CO (Valentine and Zepp, 1993;Miller and Zepp, 1995;Stubbins et al, 2006b). Photoproduction is the dominant source of CO in natural waters and results in the supersaturation of surface waters with CO and CO emission to the atmosphere (Conrad et al, 1982;Bates et al, 1995;Stubbins et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%